Neuroticism modulates mood responses to pharmacological sex hormone manipulation in healthy women. (January 2019) - Stenbæk, D.S.; Budtz-Jørgensen, E.; Pinborg, A.; Jensen, P.S.; Frokjaer, V.G.
Highlights: Neuroticism modulates mood responses to pharmacological sex hormone manipulation. Both high and low Neuroticism is associated with more pronounced mood changes. Mood responses appear to peak with gonadal stimulation and not gonadal suppression. Neuroticism modulates mood responses independent of in vitro fertilization stress. Abstract: Background: Women show increased risk of depressive symptoms during hormonal transition phases. The risk mechanisms may include changes in mood in response to fluctuating ovarian hormones moderated by predisposing risk factors for mood disorders, such as personality trait Neuroticism. Methods: A pooled sample of 92 mentally healthy women (28.3 ± 7.1, mean age ± SD) from two independent cohorts run in our lab, using gonadotropin-releasing hormone agonist (GnRHa) experimentally (n = 28) compared to placebo (n = 27) and as part in vitro fertilization (n = 37), were extracted from the Center for Integrated Molecular Brain Imaging database. All women filled in questionnaires of trait Neuroticism from the NEO personality Inventory-Revised (NEO PI-R) at baseline and self-reported levels of mood disturbances with the Profile of Mood States (POMS) daily during 14 days of GnRHa intervention or placebo. Effects of intervention by trait Neuroticism on serial daily reports of mood disturbances were examined using mixed model analyses. Results: Personality trait Neuroticism significantly modulated daily mood responses to GnRHa, but not placebo. Women with high and low scores on trait Neuroticism at baseline experienced more pronounced changes in mood when exposed to GnRHa, whereas women with medium trait Neuroticism scores remained relatively stable. Conclusions: The susceptibility to hormone-triggered mood changes appears to depend upon women's general tendency to experience distress and destabilization of mood, as captured by personality trait Neuroticism. This could aid clinicians evaluate hormone-related vulnerability for mood disorders in women and may guide targeted prevention in reproductive care.